2017
DOI: 10.4049/jimmunol.1601855
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Systems Analysis of Human Blood Reveals Immature Neutrophils in Males and During Pregnancy

Abstract: Despite clear differences in immune system responses and in the prevalence of autoimmune diseases between males and females, there is little understanding of the processes involved. Here, we identified a gene signature of immature-like neutrophils (Immature-Like Neutrophil Signature, ILNS), characterized by the overexpression of genes encoding for several granule-containing proteins, which was found in higher levels (up to 3-fold) in young (20 – 30 years old) but not older (60 – >89 years old) males compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 92 publications
4
63
0
1
Order By: Relevance
“…S1 and Fig. S2) who had been recruited at Stanford University (the Stanford 1000 Immunomes Project, or Stanford 1KIP) for a longitudinal study of aging and vaccination (Blazkova et al, 2017;Brodin et al, 2015;Furman et al, 2017b;Furman et al, 2014;Furman et al, 2013;Furman et al, 2015;Price et al, 2013;Roskin et al, 2015;Shen-Orr et al, 2016;Wang et al, 2014), and for an independent study of chronic fatigue syndrome (Montoya et al, 2017), from which only healthy controls were included. Inclusion and exclusion criteria can be found under the Methods section.…”
Section: Study Design Of the Stanford 1000 Immunomes Projectmentioning
confidence: 99%
See 2 more Smart Citations
“…S1 and Fig. S2) who had been recruited at Stanford University (the Stanford 1000 Immunomes Project, or Stanford 1KIP) for a longitudinal study of aging and vaccination (Blazkova et al, 2017;Brodin et al, 2015;Furman et al, 2017b;Furman et al, 2014;Furman et al, 2013;Furman et al, 2015;Price et al, 2013;Roskin et al, 2015;Shen-Orr et al, 2016;Wang et al, 2014), and for an independent study of chronic fatigue syndrome (Montoya et al, 2017), from which only healthy controls were included. Inclusion and exclusion criteria can be found under the Methods section.…”
Section: Study Design Of the Stanford 1000 Immunomes Projectmentioning
confidence: 99%
“…The Stanford 1KIP consists in 1001 ambulatory individuals (339 males and 662 females) recruited at Stanford University during the years 2007 to 2016 for various studies of aging and vaccination (N = 605) (Blazkova et al, 2017;Brodin et al, 2015;Furman et al, 2017b;Furman et al, 2014;Furman et al, 2013;Furman et al, 2015;Price et al, 2013;Roskin et al, 2015;Shen-Orr et al, 2016;Wang et al, 2014), and for an independent study of chronic fatigue syndrome (Montoya et al, 2017), from which we utilized data from the control set of participants only (N = 396). diabetes mellitus treated with insulin, moderate to severe renal disease, blood pressure >150/95 at screening, chronic hepatitis B or C, recent or current use of immunosuppressive medication.…”
Section: The Stanford 1000 Immunomes Study Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…It increases dramatically during pregnancy to more than 4-fold on average. This is likely in part due to the known increase in neutrophil numbers in the peripheral blood during the 2nd and 3rd trimesters, but likely also reflects changes in neutrophil function as previously observed [28]…”
Section: Longitudinal Monitoring Of Immune Status In Pregnancymentioning
confidence: 62%
“…Particularly relevant in the field of autoimmune diseases, since most of these are sex biased, are the differences in the activity of immune cells in males versus that in females. Applications of systems immunology to this area have just begun, and initial data show gross sex differences for healthy young adults, but for not older adults, in particular subsets of cells, including blood neutrophils, in their maturation status and responses to sera from patients with systemic lupus erythematosus 64 that were previously unappreciated. In the domain of systemic lupus erythematosus, work has shown that the application of systems approaches to these patients enables accurate identification of molecular networks that stratify disease activity 65 .…”
Section: Autoimmunitymentioning
confidence: 99%